Faktor-faktor kelewatan dalam projek pembinaan bangunan pendidikan MARA - Alias, Idris (2006)
It is quite common phenomenon for government projects to experience delay. Numbers of studies been carried out to investigate the matter. The attitude of contractors possibly contributed to delay in project delivery. Similar attitude also significantly affecting MARA Educational projects. This study explores sources of delay in the completions of MARA Educational projects. Conceptually, this study highlights three types of delay, compensable delay, excusable delay and nonexcusable delays. A survey on architects and project consulting for MARA projects had successful shown that for 14 educational projects, the most critical leading factors are increase in prices of materials and failure to comply to the working schedule. Additionally, shortage in professional team, unsystematic site management and delay in appointing sub contractor have also contributed to delay. As the analysis indicates that considered in granting Extension of Time (EOT) included infrastructure works, changes in design, material shortage and Variation Order (VO). It is clear that apart from weather and materials delays are contributed by contractors and client. Therefore MARA must ensure that only capable contractors will be appointed in MARA’s project undertaking. More importantly, MARA must be aware and consistent with theirs needs so as not to impose much changes during constructions. Thus a good cooperation is needed to ensure the successfully completed projects could be delivered and benefited by the community.